Tio2 Nanocomposites And Its Applications; A Brief Review - et. al., Gangesh Krishna G, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Among the nanoparticles of metallic and metal oxides (NPs), like titanium dioxide NPs, there are even more polymeric NPs, liposomes, micelles, quantum dots, dendrimers, or fullerenes. Regarding the possible usage in innovative medical treatments, they are more significant. TiO2 is an inorganic material which owes its recent increase in scientific value to with photocatalytic activity. TiO2 generates an array of reactive oxygen species (ROS) after lighting in aqueous media of UV light. Photodynamic therapy (PDT) has been used to treat various types of diseases, from psoriasis to cancer, with the capacity to produce ROS and thus induce apoptosis. NPs of titanium dioxide have been investigated as photosensitizing substances in the management of malignant tumors and photodynamic detoxification of bacteria immune to antibiotics. As photocatalysis in PDT, both TiO2 NPs itself, and also their composites and mixes with other compounds or organic compounds, could be used effectively. In addition, numerous natural on TiO2NPs, substances can be grafted, contributing to hybrid materials. These nanostructures will reveal enhanced absorption of light, enabling their future usage in medication in targeted therapy. Many strategies using TiO2 have been studied to boost successful antitumor and antibacterial therapies. In this study, the findings of selected studies describing the variety of possible uses are addressed.